Challenges to Law in the Era of Digitization (on the Example of the Republic of Belarus) - Shafalovich, Hanna (Teisė, 2020)
Despite the fact that digital technologies even in a short time change various aspects of social relations, law, as a normative structure, remains something like the last bastion of conservatism. The development of adequate answers to numerous challenges to the development of law in the context of digitalization should begin with the identification and awareness of these challenges, which this article is intended to make.